Estudio comparativo de los sistemas integrados de información de multas y sanciones por infracciones de tránsito en la ciudad de Bogotá D.C (2022)
This degree project carried out at the ANTONIO NARIÑO UNIVERSITY (UAN) proposes a comparative study of the integrated information systems for fines and sanctions for traffic violations in the city of Bogotá D.C, a problem that is experienced daily, due to the subpoenas and fines imposed on citizens, which are imposed for different reasons such as: driving while intoxicated, speeding or violating traffic regulations. To carry out this study, various sources of information that compile information on urban mobility in relation to the imposition of subpoenas, infractions and fines that allow interpreting the regional and national context were analyzed. As a result of the information analysis, differences were found in the figures published by the public authorities, regarding the count of fines and infractions imposed for the period 2015 to 2021, which leads to conclusions about the imprecision in the data and how it can affect decisions and investigations carried out based on these sources of information.